Morphological and morphometrical identification of Meloidogyne populations from various crop production areas in South Africa with emphasis on M. enterolobii - Rashidifard, Milad; Fourie, Hendrika; Daneel, Mieke Stefanie; Marais, Mariette (Zootaxa, 2019)
Accurate identification of Meloidogyne spp. is crucial and the first step to apply suitable management strategies to combat these nematode pests. Perineal-pattern morphology of female specimens is one of the most common characteristics used for identification. However, for some species various morphological characteristics are similar which makes it challenging to correctly identify species. In this study different morphological and morphometrical characteristics were used to identify 37 populations of Meloidogyne obtained during 2015 and 2016 from various crop production areas situated across different geographical regions in South Africa. A comprehensive study of females, males and second-stage juveniles (J2) of the 37 Meloidogyne populations isolated was conducted, revealing the presence of Meloidogyne enterolobii, M. hapla, M. incognita and M. javanica. Although three perineal-pattern characteristics proved to be useful in discriminating particularly between M. enterolobii and M. incognita females, most of the morphometric characters used to identify female, male and J2 individuals overlapped among the different species. Substantial intraspecies variation was also evident among different populations. The use of classical identification approaches alone could therefore not clearly distinguish among the 37 Meloidogyne populations studied. Therefore, the use of molecular techniques in combination with morphological and morphometrical analyses is suggested to be more accurate and reliable in discriminating between Meloidogyne spp.